CONTENT CHANGES OF NATRIUM CHLORIDE AND NITRATES DURING MATURATION PERIOD IN FERMENTED SAUSAGES - Joshevska, Elena (Horizons - International Scientific Journal, 2021)
The paper presents the dynamics of changes in the content of natrium chloride and nitrates in fermented sausages produced in the local meat industry, from the beginning until the end of maturation period (3; 7; 14; 20-day). Sausages are produced using Glucon Delta Lactone (GDL) additive and starter cultures. The addition of natrium chloride and nitrates has great influence of the overall enzymatic process and of the achieved degree of ripening and drying. In relation to the content of salt, the produced sausages are in accordance with the production technology and in accordance with the Rulebook for Quality of the products produced outside our country.